Phenotyping bananas for drought resistance - Ravi, Iyyakutty; Uma, Subbaraya; Vaganan, Muthu M.; Mustaffa, Mohamed M. (Frontiers in Physiology, 2013)
Drought has emerged as one of the major constraints in banana production. Its effects are pronounced substantially in the tropics and sub-tropics of the world due to climate change. Bananas are quite sensitive to drought; however, genotypes with ‘B’ genome are more tolerant to abiotic stresses than those solely based on ‘A’ genome. In particular, bananas with ‘ABB’ genomes are more tolerant to drought and other abiotic stresses than other genotypes. A good phenotyping plan is a prerequisite for any improvement program for targeted traits. In the present article, known drought tolerant traits of other crop plants are validated in bananas with different genomic backgrounds and presented. Since, banana is recalcitrant to breeding, strategies for making hybrids between different genomic backgrounds are also discussed. Stomatal conductance, cell membrane stability, leaf emergence rate, rate of leaf senescence, RWC and bunch yield under soil moisture deficit stress are some of the traits associated with drought tolerance. Among these stress bunch yield under drought should be given top priority for phenotyping. In the light of recently released Musa genome draft sequence, the molecular breeders may have interest in developing molecular markers for drought resistance.